Homoeologous Chromosome Sorting and Progression of Meiotic Recombination in Brassica napus: Ploidy Does Matter!. Issue 4 (15th April 2014) - Grandont, Laurie; Cuñado, Nieves; Coriton, Olivier; Huteau, Virgine; Eber, Frédérique; Chèvre, Anne Marie; Grelon, Mathilde; Chelysheva, Liudmila; Jenczewski, Eric
Abstract : Comparisons of meiosis in near-isogenic allohaploid and euploid lines of B. napus reveal that the mechanism that promotes efficient chromosome sorting in euploids is adjusted to promote crossover formation between homoeologs in allohaploids. This suggests that, in contrast to other polyploid species, in B. napus, chromosome sorting depends on context. Abstract: Meiotic recombination is the fundamental process that produces balanced gametes and generates diversity within species. For successful meiosis, crossovers must form between homologous chromosomes. This condition is more difficult to fulfill in allopolyploid species, which have more than two sets of related chromosomes (homoeologs). Here, we investigated the formation, progression, and completion of several key hallmarks of meiosis in Brassica napus (AACC), a young polyphyletic allotetraploid crop species with closely related homoeologous chromosomes. Altogether, our results demonstrate a precocious and efficient sorting of homologous versus homoeologous chromosomes during early prophase I in two representative B. napus accessions that otherwise show a genotypic difference in the progression of homologous recombination. More strikingly, our detailed comparison of meiosis in near isogenic allohaploid and euploid plants showed that the mechanism(s) promoting efficient chromosome sorting in euploids is adjusted to promote crossover formation between homoeologs in allohaploids. This suggests that, in contrast to other polyploid species, chromosome sorting is context dependent in B. napus .